Pelatihan Pembuatan Essential Oil dan Aplikasinya di UPT. PS. Anak dan Remaja Dinas Sosial Tanjung Morawa - Permata, Yade Metri; Tanjung, Hari Ronaldo; Khairunnisa, Khairunnisa; Nasution, Lisda Rimayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Essential oil is used as a complementary therapy for relaxing the body, food additives, cosmetics, or fragrances. Essential oil has antioxidant, anti-inflammatory, antimicrobial, and other biological activity. Essential oil and its constituents enhance penetration of the active substance into the skin cause of evaporate and excrete easily. The youth at UPT.PS.Anak Remaja Dinas Sosial Tanjung Morawa have a lack knowledge and skills about the utilization of essential oil and its processing into health and beauty products. This activity aims to enhance the knowledge of youth at UPT.PS.Anak Remaja Dinas Sosial Tanjung Morawa about benefits and methods of obtaining and processing essential oils into health and beauty products. This activity was conducted by lecture method, followed by workshop and practical preparation. The enthusiasm of participants was demonstrated by their active role in the lectures and workshops. Through the implementation of this activity, the youth at UPT.PS.Anak Remaja Dinas Sosial Tanjung Morawa have been able to improve the economic value and skills when completing their construction.